Literature Review on Empowering MSMEs in Supporting National Economic Resilience and Growth - Muhammad Alif Muaffa; Furqanul Amirur Rifan; Mashudi (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting Indonesia's economy, especially in the context of global crises and pandemics that test national economic resilience. This study aims to examine effective empowerment strategies for MSMEs that support resilience and drive sustainable national economic growth. The method used is a literature study with a qualitative approach, collecting and analyzing various academic references from journals, reports, and official documents. The results of the review show that empowering MSMEs through improved management governance, digitalization, and socio-economic integration can enhance community welfare and the competitiveness of small enterprises. However, challenges such as limited access to information, uneven training distribution, and regulatory barriers remain major obstacles. In conclusion, synergy between the government, society, and the private sector, as well as adaptive and inclusive policies, is required to create a sustainable MSME empowerment ecosystem. The study also recommends further exploration of the role of local expertise in empowerment strategies.